Granulosis Rubra Nasi (GRN): A Rare Case Report - Alshami, Mohammad Ali; Mohana, Mona Jameel; Alshami, Ahlam Mohammad (Achievements and Challenges of Medicine and Medical Science Vol. 10, 2025)
Granulosis Rubra Nasi (GRN), an extremely rare autosomal dominant genodermatosis, was first described by the German dermatologist Josef Jadassohn in 1901. It affects the eccrine glands of the central face (nose, cheek, and chin), usually manifesting during early childhood, but sometimes in adolescence, and adulthood. A 10-year-old Yemeni boy presented to the dermatology department with a 4-year history of localized hyperhidrosis, erythema, and telangiectasias over the tip, dorsum, and alae of the nose. On cutaneous examination erythema, covered with beads of sweat, telangiectasias, multiple 2-4 mm transparent cysts, and a few erythematous papules were present on the lateral sides and alae of the nose. The study concluded that an increased awareness of the dermatologist about this condition will lead to early diagnosis. Future research should focus on elucidating the gene involved, the pathophysiology, and new treatments of GRN, which is usually not needed and reassurance of the patient is enough, as it is self-limited and disappears during puberty.